Síntese, avaliação farmacológica e estudos computacionais de dímeros de tacrina - Roney Anderson Nascimento de Aquino (2014)
This work presents the synthesis of fifteen new tacrine dimers and results for Ki, IC50, kinetic mechanism and molecular docking analysis in relation to cholinesterases; and the assessment results of the antitumorigenic activity of these new molecules for ten representative cell lines as well as modeling. Tacrine dimers were obtained in good yields (78% on average) being the lowest yield (43%) for compound 24 (naphthalene spacer) and the highest yield (98%) for compound 21 (benzidinic spacer). These good yields can be understood in terms of activation of the nucleophilic aromatic substitution reaction by pyridine nitrogen. Moreover, the availability of nonbinding electron pair of the amine spacer associated to the appropriate molecular orientation at the time of reaction seem important for the efficiency of the reactions where steric effects and conformational restriction seems to determine the occurrence of the process. Moreover, crystallization is a more effective technique to obtain higher yields of reaction. In enzymatic assays, the dimers obtained were cholinesterase inhibitors in a nanomolar order. The most potent AChE inhibitor was compound 15 (Ki EeAChE = 0.61 nM) whereas for BChE was compound 16 (Ki hBChE = 3.14 nM). Within the dimers with aromatic spacers, the highest inhibitory potency was achieved by compound 21 (Ki hAChE = 2.67 nM), being this compound one with better selectivity profile for hAChE (44 times more selective). In contrast, the best selectivity profile for hBChE was reached by the dimer 25 with naphthalene spacer (38 times more selective). Thus, aromatic spacers are useful strategy for establishing interaromatic interactions with the middle region of the enzyme gorge, allowing modulating the selectivity of ligands. Furthermore, as in the case of compound 16, the expansion of the hydrophobic region of tacrine dimers can enlarge their inhibitory capacity. Similar to tacrine, it was observed that their dimers are mixed inhibitors, and performance data obtained on the evaluation of inhibitory activity against non-human cholinesterase can be extended to the expected power to human cholinesterase. Finally, as observed for compound 15, the parameters of optimal length (10Å) and structural flexibility of the spacers are essential to the effectiveness of cholinesterase dual inhibitors. The antitumorigenic activity evaluation showed that the tacrine dimers have IC50 in the micromolar order on average, being the compound 16 the most potent (IC50 SKMEL5 < 7.5 nM), besides being the most potent compound for the cell lines IMR32, SKOV3, SKMEL2, BT549 and U87MG. Among the compounds with aromatic spacers, compound 26 is of broader spectrum being more potent than compound 16 for C6, TOV21G and COLO205 cell lines. Tacrine was found to be inactive in all tested cell lines. Tacrine dimers presented with significant selectivity profile for some cell lines, the compound 16 being more selective for SKMEL5 at least one order of magnitude. Moreover, tacrine dimers may combine selective cytotoxicity with cholinergic system manipulation. In addition, tacrine derivatives may have significant ability to interact with multiple DNA targets, in addition to tubulin and multidrug transporter, and, although this interaction capability not present simple correlations with in vivo activity, there are possibilities for establishing structure-activity relationships. In this context, it is noted that the nature (alkyl versus aromatic) and spacer length and the size of the alicyclic ring (5, 6, or 7 carbons) from tetrahydroacridine component of dimers appear to be among the factors that modulate the cytotoxicity of this class of molecules. This can be inferred from the variations observed in cytotoxic activities of dimers, their interaction energies and possible association conformations with biomolecules.